Exploring the Longitudinal Links Popularity Goals and Adolescent Cyberbullying Perpetration: The Moderating Effects of Gender and Cultural Context - Michelle F. Wright (MDPI AG, 2024)
Background/Objectives: This longitudinal study aimed to examine how gender influences the relationship between popularity goals and cyberbullying perpetration among adolescents in China and the United States, controlling for peer-nominated popularity. Additionally, the study sought to identify potential cross-cultural differences in these dynamics. Methods: The research involved 1063 eighth and ninth graders (ages 12-16; 48.7% girls) who completed self-reported surveys in the fall of 2022 (Time 1) regarding cyberbullying behaviors and popularity goals. Peer nominations of popularity were also collected. Follow-up data on cyberbullying perpetration were obtained one year later in the fall of 2023 (Time 2). Results: Popularity goals were found to positively predict cyberbullying perpetration at Time 2 across all participants even after accounting for peer-nominated popularity. In China, this association was more pronounced among boys, whereas in the United States, the relationship was stronger for girls. Conclusions: Although cultural differences in the overall patterns were minimal, gender emerged as a significant moderating factor, revealing distinct cross-cultural variations. These findings underscore the need for culturally tailored approaches in interventions targeting adolescent cyberbullying.